As dimensões geográficas dos Arranjos Produtivos Locais - Labigalini Fuini, Lucas (Pontifica Univ Catolica Chile, Inst Geografia, 2014)
This article aims to further discuss the Local Productive Arrangements (APLs), considering some geographical visions thinking about spatial configuration and the economic and social processes that characterize them, configuring a wide range of territorialities and productive territories that mark the landscape current Brazilian. In this sense, APLs are present today in both the figure of those who study analytical concept for regional development, and as a public policy supporting networks and supply chains in their territorial bases, especially small businesses. Thus, this arrangements can be read, geographically, as territorial productive specializations that are configured in spatial circuits of production, integrated with other regions, localities and supply chains through the morphology of networks and districts and grounded in networks of urban networks of material and immaterial flows which are bringing urban centers of different sizes. Considering the multidimensionality of the subject, the clusters have certain weaknesses in terms of their assumptions and perspectives, especially the limitations of the tool if designed just for resources and policies applied at the local level. Suggest the approach of a "geography of APLs" is to seek treat it from a territorial and socio reading.

O presente artigo tem como objetivo aprofundar a discussão sobre os Arranjos Produtivos Locais (APLs), considerando determinadas visões geográficas a pensar sobre a configuração espacial e os processos econômicos e sociais que os caracterizam, visto que configuram uma ampla gama de territorialidades e territórios produtivos que demarcam a paisagem brasileira atual. Nesse sentido, APLs estão presentes na atualidade tanto na figura de conceito analítico para quem estuda o desenvolvimento regional, quanto como política pública de apoio às redes e cadeias produtivas em suas bases territoriais, sobretudo de pequenos negócios. Assim, esses arranjos podem ser lidos, geograficamente, como especializações territoriais produtivas que comportan como circuitos espaciais de produção, integrados à outras regiões, localidades e cadeias produtivas através da morfologia de redes e de distritos, e alicerçados em sistemas e redes urbanas de fluxos materiais e imateriais que fazem aproximar centros urbanos de diferentes dimensões. Considerando a multidimensionalidade do tema, os APLs apresentam certas fragilidades do ponto de vista de seus postulados e perspectivas, sobretudo pelas limitações da ferramenta se pensada apenas em recursos e políticas aplicada no nível local. Sugerir a abordagem de uma "geografia dos APLs" é buscar tratá-lo a partir de uma leitura territorial e socioespacial.
The geographic dimensions of local productive arrangements
Keywords: Local productive arrangements; Space circuit production; District networks; Urban network; Territorial productive specialization; Arranjos produtivos locais; Circuito espacial de produção; Redes de distritos; Rede urbana; Especialização territorial produtiva